Alterung und Ästimation des Zustands von Papier-Masse-Kabeln in Mittelspannungsnetzen - Mladenovic, Ivana; Scharrer, Thomas; Weindl, Christian (Elektrotechnik und Informationstechnik, 2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.leen.alteru

Analyse des Alterungsverhaltens von MS-Papier-Massekabeln unterschiedlicher Generationen anhand der Rückkehrspannung - Weindl, Christian; Mladenovic, Ivana; Scharrer, Thomas; Patsch, Rainer (VDE-Kongress: Diagnostik elektrischer Betriebsmittel, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.leen.analys

An Interpretation Approach for in FieldMeasured Dissipation Factor Values of MV Cable Lines - Freitag, Christian; Mladenovic, Ivana; Weindl, Christian (11th IEEE International Conference on Solid Dielectrics, 2013)
In modern power utilities attention is especially directed to the condition determination of the network's electrical equipment, with the purpose of supporting the condition oriented asset management and maintenance strategies. In medium voltage (MV) networks, cables require the biggest investment capital. In order to point out the most suitable diagnostic parameters and their limits, a long lasting accelerated and artificial ageing experiment on MV paper insulated lead covered (PILC) cables was performed. The in this way determined dependencies of the diagnostic parameters on voltage, temperature and condition of the cables, as well as characteristic values and regarded failure probability play an immense role in the determination of cables' condition in field measurements. Still, the diagnostic criterion (e.g. in case of dissipation losses comparison of: absolute value, hysteresis, dependency on testing voltage) could significantly influence the final diagnostic statement. In addition, the recorded values have to be evaluated regarding the composition of the cable line. This problematic will be shown in the article and discussed on several exemplar field measurement
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.leen.aninte
Keywords: Power cables; Voltage measurement; Power cable insulation; Correlation coefficient; Dielectrics; Temperature measurement

Bestimmung von Restlebensdauer von Massekabeln anhand einer Teilentladungs- und tan(delta)-Diagnose - Weindl, Christian; Mladenovic, Ivana (Internationaler ETG-Kongress 2009, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.leen.bestim_8

Comparison of parametric Partial Discharge and Dissipation Factor Characteristics of MV PILC Cables - Mladenovic, Ivana; Weindl, Christian; Freitag, Christian (ISEI, 2012)
Within a long-lasting project, differently pre-aged, as well as brand new medium voltage (MV) paper insulated lead covered cables (PILC) have been artificially aged. Hereby, the dissipation factor and the partial discharges (PD) have been regularly monitored over the complete lifetime of the accelerated aged samples. Additionally, measurement cycles with varied temperatures and voltages have been accomplished in regular time intervals. All measurements were carried out with the network frequency of 50 Hz. In this paper, the results of parametrical studies over a set of predefined voltages (0.4·times nominal voltage up to 2.2·times) and cable temperatures (15°C to 85°C), accomplished under defined and monitored environmental conditions, will be presented and discussed. Additionally, possible correlations of the PD activity and its intensity on the functional characteristic of tan(δ) will be analyzed by the use of three-dimensional parametrical comparison studies. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.leen.compar
Keywords: ageing; cable; diagnostic; dissipation factor; partial discharge

Dependencies of PD and tan(delta)-Characteristics o the Temperature and Ageing Status of MV PILC Cables - Mladenovic, Ivana; Weindl, Christian (EIC 2011, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.leen.depend

Dependency of the Dissipation Factor on the Test-Voltage and the Ageing Status of MV PILC Cables - Mladenovic, Ivana; Weindl, Christian (Jicable, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.leen.depend_0

Determination of the Characteristic Life Time of Paper-insulated MV-Cables based on a Partial Discharge and tan(delta) Diagnosis - Mladenovic, Ivana; Weindl, Christian (13th International Power Electronics and Motion Control Conference EPE-PEMC 2008, 2008)
Monitoring the condition of electrical equipment insulation by means of partial discharge measurement and analysis is an effective diagnostic tool for the prediction of service failures. In this paper an accelerated aging system specialized for paper insulated lead covered (PILC) cables, with a highly sensitive and selective PD-detection/localization and tan(δ) measurement is presented. It facilitates the monitoring of the entire aging process and the later development of sophisticated diagnostic criteria based on the physical aging process. © 2008 IEEE.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.leen.determ
Keywords: Diagnostics; Estimation technique; Insulation; Maintenance; Measurement; Partial discharge; Prognosis; Software for measurements

Determination of the Environmental Conditions for the Accelerated Ageing of MV-PILC Cables - Mladenovic, Ivana; Weindl, Christian (Proceedings of the the 9th International Conference on Properties and Applications of Dielectric Materials ICPADM 2009, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.leen.determ

Determination of the Remaining Lifetime of Paper Insulated Lead Covered Cables based on the Diagnostics of Partial Discharges and the Dissipation Factor (Bestimmung der Restlebensdauer von Papier-Masse-Kabeln mit Bleimantel auf der Grundlage einer Teilentladungs- und Verlustfaktordiagnostik) - Mladenovic, Ivana (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2013)
UnivIS-Import:2016-07-26:Pub.2013.tech.IE.leen.determ

Development of the Partial Discharges Inception Voltage for Different Sets of Pre-Aged PILC Cable Samples - Mladenovic, Ivana; Weindl, Christian (ISEI 2010, 2010)
Diagnostics and the rest life time estimation of the electrical equipment play an important role in the power network investment and maintenance planning. In order to develop a reliable correlation between the partial discharges and the time to the next failure of the MV PILC cables, a special system called ICAAS (Integrated Cable Accelerated Aging System) for the artificial accelerated aging was developed. The aging system includes highly sensitive and selective PD-detection and tan(δ)-measurement units. During the entire aging process, a knowledge data-base will be formed up, by the constant monitoring of all relevant aging parameters and measured values. The functionality of the ICAAS was confirmed in a pre-test and the most suitable ageing and physical parameters for the main aging experiment, which should last for two years in continuity, were determined. Therefore two different sets of cable samples were used in the pre-test. Group one was made up of samples of brand new cables, in a second group nine 20 years old cables were aged, including cables with an existing and defined partial discharge level. In this paper the results, by meaning of partial discharge activities and environmental influence of the pre-test will be shown and discussed. The physical processes that appear in the cable insulation of PILC cables will be discussed, and in this way the limitations in the electrical aging parameters. ©2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.leen.develo_8
Keywords: Artificial aging; Diagnosis; Inception voltage; MV cable; Partial discharge; Rest life time

Development of the p-factor in an Accelerated Ageing Experiment of the MV PILC Cables - Weindl, Christian; Mladenovic, Ivana; Scharrer, Thomas; Patsch, Rainer (ICSD, 2010)
Insulation materials deteriorate with time due to numerous operational and environmental influences. Owing to thermal and electrical ageing, moistening, etc., several chemical and physical deterioration processes in the insulation materials arise, which result in the decrease of the electrical strength and influence dielectric processes and characteristics like conduction processes and the polarization of the insulation. By using the return voltage method (RVM) it is possible to determine probable decrease in electrical strength without damaging. This method has been shown as very appropriate particularly in the case of cables with impregnated paper insulation. MV PILC (medium voltage paper insulated lead covered) cables and its remaining time of life are in the focus of an international research project for which purpose an automated ageing system called ICAAS (Integrated Cable Accelerated Ageing System) was developed. The RVM method was applied on specially selected samples of the entire test field with an average operation age of 20, 40 and 60 years. All Cables in the test field will be artificially and continuously aged in the ICAAS for around two years. In this article the results of the initial return voltage measurements are presented and discussed. The measurements were repeated in defined time intervals, and the influences of the ambient temperature and the air humidity were monitored. The return voltage curves under different conditions and corresponding p-factors were determined and shown. ©2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.leen.develo
Keywords: Ageing; Diagnostic; P-factor; PILC cable; Power cable; Return voltage; Return voltage method

Developments in the Diagnostics of MV PILC Cables - Mladenovic, Ivana; Weindl, Christian (IEEE Electrical Insulation Magazine, 2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.IE.leen.develo

Effects of MV PILC Cables Ageing Process on the Diagnostic Parameters: p-factor and tanδ - Mladenovic, Ivana; Weindl, Christian; Scharrer, Thomas (11th IEEE International Conference on Solid Dielectrics, 2013)
During field operation, power equipment is exposed to numerous impacts (especially thermal and electrical stress), which result in a continuous deterioration of its insulation material. The grade of the deterioration can be weighted by different diagnostic measurements. Within an accelerated ageing experiment on paper insulated lead covered (PILC) cables, several diagnostic parameters have been measured regularly during the ageing process of ca. 2 years. The cable samples are PILC cables (20 kV, 150 mm2) of 13 m length, which are differently pre-aged (from brand new, up to cables that have been in operation for 60 years). In this article aging effects of this insulation system on dissipation factor and parameters of return voltage curve as well as on p-factor will be shown and discusse
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.leen.effect
Keywords: medium voltage cable; PILC cable; diagnostics; ageing; dissipation factor; return voltage

Einfluss vermaschter Topologiekonzepte auf die Netzplanung unter Berücksichtigung der Schutzkoordination - Wolter, Daniel; Biller, Martin; Schacherer, Christian; Mladenovic, Ivana; Zdrallek, Markus; Jäger, Johann (15. Symposium EnergieInnovation, 2018)
Keywords: Mittelspannungs-Netzplanung; Schutzkoordination; Topologiekonzepte; Vermaschung

Empiric Approach for Criteria Determination of Remaining Lifetime Estimation of MV PILC Cables - Mladenovic, Ivana; Weindl, Christian (Dielectric Material, 2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.IE.leen.empiri

Empiric Approach to a Condition-Oriented Maintenance and Investment Strategy for MV Cable Networks - Mladenovic, Ivana; Weindl, Christian (Clean Electrical Power, 2009)
The method and efficiency of an investment strategy is strongly dependent on the amount and accuracy of the knowledge about the actual condition of the network system. Therefore the assessment of the aging status of the network equipment and namely its rest-life time has become an important task in the last decades. In order to assume the time to the next failure an artificial ageing system for the accelerated ageing of MV cables has been realized. It is developed to model the natural ageing process of MV cables samples as close as possible to realistic conditions. Finally, under controlled electrical and environmental ageing conditions a unique data base will be set up, which can be used to estimate the most probable time to the next failure of cable systems tested in field diagnostics, based on the partial discharge (PD) and tan(δ) values delivered from the field measurements. The described ageing system will enable further researches and developments in the direction of a condition oriented maintenance strategy for MV cable networks. © 2009 IEEE.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.leen.empiri
Keywords: Aging; Assessment; Cable insulation; Failure probability; Lifetime; Medium voltage network; Partial discharge

Essential Strategies for the Remaining Lifetime Estimation of the MV Cable Systems - Mladenovic, Ivana; Weindl, Christian; Scharrer, Thomas (22. International Conference on Electricity Distribution CIRED 2015, 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.IE.leen.essent

Experiences on in Field Measured Dissipation Factor on MV PILC Cables at 50 Hz - Freitag, Christian; Mladenovic, Ivana; Weindl, Christian (22. International Conference on Electricity Distribution CIRED 2013, 2013)
In the past several years, a significant amount of diagnostic data has been collected under known and adjustable test conditions, with the purpose of improving the diagnostic possibilities for medium voltage (MV) paper insulated lead covered (PILC) cables. Beside the complexity of the interpretation processes by itself, an additional challenge of onsite measurements is the investigation of mixed cable lines, as the analysis of the results is proven to be difficult. Moreover, when interpreting the measured values, i.e. diagnostic parameters, the problem often arises that different applied diagnostic criteria (e.g. in case of dissipation losses comparison of: absolute value, hysteresis, dependency on testing voltage) result in different statements. In this paper, empirically determined dependencies of the diagnostic parameter (in front of all the dissipation factor on test conditions) as well as the results of the in-field measured values and suggestion for their interpretation are presented.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.leen.experi
Keywords: field measured dissipation factor; MV PILC cables; diagnostic data collection; medium voltage paper insulated lead covered cable; onsite measurements; mixed cable lines; diagnostic parameter; frequency 50 Hz

Fully Automated MV Cable Monitoring and Measurement System for Multi-Sample Acquisition of Artificial Aging Parameters - Freitag, Christian; Weindl, Christian; Mladenovic, Ivana (International Conference on Renewable Energies and Power Quality ICREPQ '10, 2010)
The Power quality of our networks is influenced by transients, short- and long-duration variations, voltage unbalance, waveform distortions, voltage fluctuations and power frequency variations. These impacts affect the aging rapidity of the electrical equipment and finally the entire electrical network. By partial discharge (PD) and tan(δ) analyses, it is possible to determine the electrical equipment’s condition. The significance of the results depends on the quality of the measurement system and of the data interpretation. Based on these results, a reliable maintenance and investment strategy could be made, and the reliability of the network could be improved. A specially designed aging system for the accelerated aging of MV cables has been developed to point out the most relevant aging parameters and their limits, and, in this way, to upgrade the accuracy of the MV cable diagnostics. In this paper, the system’s “intelligence”, which controls the aging process and acquires, evaluates and stores all necessary data is presente
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.leen.fullya
Keywords: CAMAC (Computer automated measurement and control); Partial discharges; Power cable insulation

ICAAS - Integrated System for lasting Accelerated Aging of MV Cables, Data Monitoring and Acquisition - Mladenovic, Ivana; Weindl, Christian (Electrical Insulation and Dielectric Phenomena, 2009)
A reliable knowledge of the network components condition is of primary importance for creating an optimal investment and maintenance plan for electrical distribution networks. A commonly used tool for this purpose is a partial discharge measurement and analysis. It enables a good overview over the electrical equipment condition and in this way also a prediction of possible service failures. In the case of paper insulated lead cover (PILC) cables, there are still no established criteria for assuming the time to the next failure. Therefore, an accelerated aging system assigned to this cable type was developed, built up and tested. It facilitates a highly sensitive and selective PD-detection and accurate tan(δ)-measurements. Furthermore, by the constant monitoring of the entire aging process, a knowledge data-base is formed up, and the later development of sophisticated diagnostic criteria based on the physical aging process is made possible. In this paper the basic principles and the functionality of a novel system for the accelerated ageing of MV cables called ICAAS (Integrated Cable Accelerated Ageing System) are presented. © 2009 IEEE .
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.leen.icaasi

Influence of the Electrical and Environmental Test-Conditions on the Characteristic Parameters of Return Voltage Curve - Mladenovic, Ivana; Scharrer, Thomas; Weindl, Christian (Conference on Diagnostics in Electrical Engineering, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.leen.influe

Influence of the thermal stress on the diagnostic parameters of PILC cables - Mladenovic, Ivana; Weindl, Christian (CMD, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.leen.influe

New System for Artifical Ageing of MV Cables under Controlled Conditions - Mladenovic, Ivana; Freitag, Christian; Weindl, Christian (20th International Conference and Exhibition on Electricity Distribution CIRED 2009, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.leen.newsys

On-Line Cable Diagnostic Possibilities in an Artificial Aging Environment - Freitag, Christian; Weindl, Christian; Mladenovic, Ivana (International Conference on Renewable Energies and Power Quality ICREPQ, 2011)
Since more than a decade the development of reliable and accurate diagnostic tools for power cables is in the centre of interest of scientists and power utilities. With the developments in our power systems, like the increasing feed-in of renewable energy sources, several issues could be additionally generated, such as extreme concurrence factors, short- and long-duration variations, voltage imbalances, waveform distortions, voltage fluctuations and power frequency variations. These impacts affect the aging rapidity of the electrical equipment and finally of the entire the electrical distribution network. Using appropriate diagnostic methods, it is possible to determine the electrical equipment’s condition. The significance of the results depends on the quality of the measurement system and of the data interpretation. Based on these results, a reliable maintenance and investment strategy could be made, and the reliability of the grid could be improved. With this goal, an accelerated aging project for MV PILC (paper insulated lead covered) cables was started. A specially designed aging system for the accelerated aging of MV cables has been developed to point out the most relevant aging parameters, their limits, their development and to upgrade the accuracy of the MV cable diagnostics in this way. In this paper, the diagnostic possibilities, mainly the dielec- tric loss factor measurement and its dependence on environmental influences are presente
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.leen.online
Keywords: diagnostics; aging; cable; partial discharge; loss factor

Protection Systems in Distribution Grids with variable Short-Circuit-Conditions - Biller, Martin; Jäger, Johann; Mladenovic, Ivana; Stötzel, Marcus; Schacherer, Christian; Wolter, Daniel (DPSD - The 13th IET International Conference on Developments in Power System Protection, 2016)

Schutz im Verteilnetz unter Berücksichtigung veränderlicher Kurzschlussleistungen - Biller, Martin; Jäger, Johann; Mladenovic, Ivana; Stötzel, Martin; Schacherer, Christian; Wolter, Daniel (9. ETG-/FNN-Tutorial für Schutz- und Leittechnik, 2016)

Sensitivity of Return Voltage and Plarization/Depolarization Current Measurements on Environmental Conditions and Test Parameters - Mladenovic, Ivana; Weindl, Christian (CMD, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.leen.sensit

Systematische Alterungsuntersuchung an Papier-Masse-isolierten Mittelspannungskabeln - Weindl, Christian; Mladenovic, Ivana; Freitag, Christian (Netzpraxis: Magazin für Energieversorgung - Planung, Bau, Betrieb, Service, 2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.leen.system_2

Verlustfaktormessung an Mittelspannungskabeln bei Netzfrequenz - Freitag, Christian; Mladenovic, Ivana; Weindl, Christian (VDE-Kongress: Diagnostik elektrischer Betriebsmittel, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.leen.verlus

Voltage- and Temperature-Dependencies of the Dissipation Factor of Pre-Aged PILC Cables - Mladenovic, Ivana; Weindl, Christian (Jicable, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.leen.voltag

Vom Alterungsversuch zur zustandsorientierten Instandhaltung - Weindl, Christian; Mladenovic, Ivana; Scharrer, Thomas (EW Magazin für die Energiewirtschaft, 2013)
UnivIS-Import:2015-03-09:Pub.2013.tech.IE.leen.vomalt